Ο Ορφέας στη νεοελληνική δραματουργία: Γεώργιος Σακελλάριος - Άγγελος Σικελιανός Γιώργος Σκούρτης - Puchner, Walter (Σύγκριση/Comparaison/Comparison, 2017)
The paper gives a short comparison of three dramatic versions of the Orpheus-myth in Modern Greek drama. Among the mythological themes dramatized in Modern Greece the most frequent is Troia cycle, the Atrides, the Argonautic cycle, heroes like Prometheus, Heracles, Theseus, Zeus etc. Orpheus is quite rare. The first analysis concerns the Greek translation of «Orphée et Euridice», the second reformation opera of Christoph Willibald Gluck, concretely the French version of Pierre Louis Moline (1774 in Paris), which is edited in Greek in Vienna 1796, and highlights the context of this translation. The second is «The Dithyramb of the Rose» (written 1932, translated in French 1933 by Louis Roussel, 1939 in English), performed 1933 in Athens, as a sort of continuation of the Delphic festivals (1927 and 1930), The third is a satiric dramatic version «The process of Orpheus and Eurydice» (1973) where Orpheus is condemned by the rulers of the Underworld because he caused troubles by his invasion with music; the one-act play has to be seen in the context of the political processes at the time of the Junta regime and is very exact in reproducing mythological details.